Switch Configuration Effect on Stray Capacitance in Electrical Capacitance Volume Tomography Hardware - Arba’i Yusuf; Harry Sudibyo S; Dodi Sudiana; Agus Santoso Tamsir; Imamul Muttakin; Wahyu Widada; Warsito P. Taruno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Electrical capacitance volume tomography (ECVT) system uses six switches in one channel with configuration resembling “T” letter, so it is called “T-switch”. The working scheme of the switch can be explained in four different modes of operation, i.e. excitation mode, detection mode, ground mode, and floating mode. This research describes the effect of switch configuration to stray capacitance in ECVT hardware. Stray capacitance introduces parasitic signal from other sources; one of them is signal from another electrode at floating mode when the signal is still flowing to detection circuit. One channel, two channels, three channels, so on until thirty-two channels are connected to single detection circuit sequentially to investigate the effect of stray capacitance. Both simulation and experiment show the stray capacitance increases along with addition of channel corresponds to 0.046pF for each channel.